A Mechanistic Review of β-Carotene, Lutein, and Zeaxanthin in Eye Health and Disease - Fatima Tuj Johra; Asim Kumar Bepari; Anika Tabassum Bristy; Hasan Mahmud Reza (MDPI AG, 2020)
Carotenoids are natural lipid-soluble antioxidants abundantly found as colorful pigments in fruits and vegetables. At least 600 carotenoids occur naturally, although about 20 of them, including β-carotene, α-carotene, lycopene, lutein, zeaxanthin, meso-zeaxanthin, and cryptoxanthin, are detectable in the human blood. They have distinct physiological and pathophysiological functions ranging from fetal development to adult homeostasis. β-carotene is a precursor of vitamin A that essentially functions in many biological processes including vision. The human macula lutea and eye lens are rich in lutein, zeaxanthin, and meso-zeaxanthin, collectively known as macular xanthophylls, which help maintain eye health and prevent ophthalmic diseases. Ocular carotenoids absorb light from the visible region (400-500 nm wavelength), enabling them to protect the retina and lens from potential photochemical damage induced by light exposure. These natural antioxidants also aid in quenching free radicals produced by complex physiological reactions and, consequently, protect the eye from oxidative stress, apoptosis, mitochondrial dysfunction, and inflammation. This review discusses the protective mechanisms of macular xanthophylls in preventing eye diseases such as cataract, age-related macular degeneration, and diabetic retinopathy. Moreover, some preclinical animal studies and some clinical trials are discussed briefly to understand carotenoid safety and efficacy.